Epidemiological Study of Gastrointestinal Helminthes of Canids in Chaharmahal and Bakhtiari Province of Iran - NABAVI, Reza (Iran J Parasitol, 2014)
BACKGROUND: The present study was carried out to describe the epidemiological aspects of gastrointestinal helminthic infections of canids in Chaharmahal and Bakhtiari Province, the central western part of Iran. METHODS: Forty nine canid species including, dogs, jackals, foxes and wolves were included in this study. The contents of their alimentary canal were inspected in order to isolate and identify the parasitic helminthes of this system. To identify the worms, the Soulsbey and Anderson identification key and light microscopy were used. RESULTS: Based on necropsy findings, 35 (71.4%) of examined animals were infected with at least one helminth. The prevalence of identified worms was as follows: Mesocestoides lineatus (55.1%), Joyeuxiella echinorinchoides (26.5%), Taenia hydatigena (12.2%), T. multiceps (8.2%), T. ovis (2%), Dipylidium caninum (2%) and Spirura spp. (2%). No significant difference was noticed between the sampling areas, age and helminth infection. Only a significant difference was observed for prevalence of T. multiceps in wolf (25%), dog (21.4%), jackal and fox (0%), respectively (P < 0.05). CONCLUSION: The canids in Chaharmahal and Bakhtiari harbor several parasites that some kind of them have zoonotic importance and may pose a threat to community health specially in rural areas.